Smoking cessation interventions in patients diagnosed with head and neck cancers: A systematic review of randomized controlled trials - Gaikwad, Rahul N.; Alqifari, Faisal; Alnasser, Mujahid; Bajad, Payal; Jain , Preet; Gondivkar, Shailesh (International Journal of Health Sciences, 2023)
Objective: According to findings from the previous studies, quitting smoking can significantly reduce mortality from all causes and is linked to better treatment results. Even though quitting smoking has many benefits, little is known about the evidence supporting the particular quit services offered to smokers after a cancer diagnosis. Methods: To find the articles related to area in question, different electronic databases including PubMed/Medline, Google Scholar, and EBSCO were searched on April 1st, 2023. All full text randomized controlled trials with one or more intervention and control groups that assessed the outcomes of smoking cessation interventions were included. Participants of included studies were adults diagnosed with head and neck cancer (HNC) and current smokers or those who had recently quit. There were interventions (pharmacological and/or pharmacological) that aimed to help patients with HNC succeed in quitting smoking. Results: We identified 15352 papers from the initial search from different electronic databases, 2560 remained after excluding duplicates. After screening titles and abstracts for relevance, 2345 articles were removed. Full text articles of remaining 215 papers were assessed in depth by two reviewers for their eligibility, amongst which, 210 articles were excluded. Finally, we included five papers that met the inclusion criteria in the present systematic review. Conclusion: According to the findings of this review, a multi - component strategy might very well benefit patients with HNC who smoke cigarettes after diagnosis. More studies with high methodological quality and standardized outcome measures must be conducted in this population to inform the development of smoking cessation program.